The revival of the nation-state? Stock exchange regulation in an era of internationalized financial markets - Susanne Lütz (Max-Planck-Institut für Gesellschaftsforschung, 1996)
The debate on economic "globalization" suggests that the blurring of territorial boundaries shifts the power relations between nation-states and domestic market constituencies in favour of the latter. States have lost autonomy since policies are increasingly formulated in supranational or global arenas. Market actors may use their wider choice of geographic location in order to lobby for low regulated market environments. The paper seeks to differentiate this common view considerably. It argues that economic internationalization weakens the capacity of domestic market actors to engage in self-binding agreements that formerly had solved regulatory problems. Networks of interstate collaboration in turn lack the ability to monitor and enforce negotiated agreements. Both developments impose new duties of market supervision on the nation-state. Empirical reference is drawn from the stock exchange sector that went through a process of transformation which has led to an enhanced role of the nation-state in the model of sectoral governance. – – Die zunehmende "Globalisierung der Ökonomie" scheint das Machtgleichgewicht zwischen Politik und Wirtschaft zugunsten der Ökonomie zu verschieben. Nationalstaaten verlieren an Autonomie, weil Politik zunehmend auf supranationaler oder globaler Ebene formuliert wird. Marktteilnehmer hingegen nutzen ihren erweiterten territorialen Aktivitätsspielraum, um staatliche Regulierungen zu umgehen, die ihre Produktionskosten erhöhen könnten. Der Beitrag will diese Perspektive differenzieren. Argumentiert wird, daß ökonomische Internationalisierung die Fähigkeit zu kollektiver Selbstregulierung der Marktteilnehmer schwächt. Netzwerken zwischenstaatlicher Kooperation auf der anderen Seite mangelt es an Kapazitäten, die Einhaltung von Vereinbarungen zu garantieren. Beide Entwicklungen führen zu neuen Aufgaben der Marktüberwachung für den Nationalstaat. Als empirisches Fallbeispiel wird der Börsensektor präsentiert, welcher weltweit einen Transformationsprozeß durchlief, aus dem erweiterte Aufgaben des Nationalstaates im Modell sektoraler Steuerung hervorgingen.
Keywords: 300